Detection of the human papillomavirus in samples obtained by self-collection technique in a group of peruvian college students - Manrique-Hinojosa, Javier (2018)
Cross-sectional study that determined the frequency and the genotypes of the (HR-HPV) high-risk human papillomavirus through the self-collection technique in a group of college students of Lima. Two hundred twenty-one (221) students participated and the DNA of the HR-HPV was detected with polymerase chain reaction (PCR). The frequency of HR-HPV in participants was 43.4%; of this group, genotype HPV 16 was present in 15.6%, HPV 18 in 4.2%, and another HR-HPV in 80.2%. We can conclude that the frequency of HR-HPV is greater in the group of college students of this study in comparison with previous national investigations.